The New Great Game : Blood and Oil in Central Asia - Kleveman, Lutz (New York Atlantic Monthly Press, 2003)
"In The New Great Game, Lutz Kleveman gives us a fearless, insightful, and exacting portrait of a new battleground in the violent politics and passion of oil: Central Asia, known as the "black hole of the earth" for much of the last century. The Caspian Sea contains the world's largest amount of untapped oil and gas resources. It is estimated that there might be as much as 100 billion barrels of crude oil in the former Soviet republics of Kazakhstan and Azerbaijan alone."
Include Notes and Index
Keywords: Petroleum Industry and Trade -- Political Aspects -- Asia, Central -- Petroleum Industry and Trade -- Political Aspects -- Caucasus -- Petroleum Industry and Trade -- Political Aspects -- Caspian Sea Region -- Caspian Sea Region -- Geopolitics